The Influence of Corporate Value and Corporate Social Responsibility Disclosure on Risk Management with Good Corporate Governance as a Moderator - Napisah, Napisah; Soeparyono, Regina Deia (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study examines the influence of corporate value and corporate social responsibility (CSR) disclosure on enterprise risk management (ERM), with good corporate governance (GCG) as a moderating variable. Using associative quantitative methods, the research analyzed panel data from 15 energy sector companies listed on the Indonesia Stock Exchange between 2019 and 2023. The findings show that corporate value does not significantly affect risk management, while CSR disclosure has a positive and significant effect on ERM. Furthermore, GCG does not moderate the relationship between corporate value and ERM, but it significantly moderates the relationship between CSR disclosure and ERM. The results suggest that GCG enhances the company’s transparency and accountability, particularly in aligning CSR practices with effective risk mitigation. The study supports the agency theory perspective, emphasizing the role of information disclosure in minimizing asymmetries between management and stakeholders. Overall, the research highlights the strategic importance of CSR and governance quality in strengthening corporate risk management practices in Indonesian energy firms.